An exploration on human compatible artificial bone placement through cell culture - Das, Sourav Kumar; Zhang, Qiang (Mediscope, 2021)
The artificial bone replacement material showed significantly higher retention forces than actual bone samples. Trauma, cancer, ageing and genetic diseases, and tissue reconstruction causes bone defects and bone lesions. Providing mechanical and functional integrity is an important step for the bone regeneration. Using autogenic or allogeneic bone grafts conventionally accelerates bone regeneration with minimal autograft and allograft capital. While autogenous graft is considered the golden standard in restoring bone defects, the harvest may impact patients. The aim of this study was to elucidate the ability of a newly developed, high porosity unidirectional porous b-TCP artificial bone to induce regeneration of bones. The capacity of a commercially available b-TCP drug to cause bone regeneration was contrasted.Implantation in bony defects left after fibula harvesting for spinal fusion surgery as well. Innovative biomaterials with osteoinductive potential have emerged as candidates for bone repair since the discovery of osteoinduction in the early 20th century. Recently, models of artificial protocell have shown great potential for tissue regeneration. Hydroxyapatite (HAP) nanocrystallites of all forms of bones are characterized by their ultrathine properties, which are uniaxially aligned with fibrillar collagen to reveal the (100) faces in a special way. We speculate that living organisms prefer the specific crystal morphology and HAP's orientation due to interactions at the mineral-cell interface between cells and crystals. To investigate the ultrathine mineral modulating effect on cell bioactivity and bone generation, bone-like platy HAP (p-HAP) and two different rod-like HAPs have been synthesized here. The platy HAP with (100) faces significantly promoted cell viability and osteogenic differentiation of mesenchymal stem cells ( MSCs) as compared to rod-like HAPs with (001) faces as the dominant crystal orientation, indicating that MSCs could recognize the crystal face and prefer the (100) HAP faces. Mediscope Vol. 8, No. 1: January 2021, Page 7-18